2009
DOI: 10.1161/circimaging.109.850263
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Imaging

Abstract: Despite the epidemiological insights from the Framingham Study 1 in the early 1950s and the resulting significant advances in the diagnosis and management of coronary heart disease (CHD), it remains the leading cause of death in the United States. In part, this is because sudden cardiac death is the first presentation of CHD in 50% of men and 64% of women 2,3 and, therefore, the only available strategy for reducing mortality in these patients is primary prevention. This is the target population for atheroscler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 115 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…3 This is particularly critical for using imaging for screening purposes among asymptomatic individuals where improved patient outcome must be weighed against risks from imaging and intervention. 93 Thus, a staged approach is likely necessary with the least costly and most benign techniques applied to patients of seemingly low risk for screening purposes and advanced imaging reserved for those deemed at higher risk. For example, ultrasound imaging of carotid artery wall thickness provides prognostic information on acute coronary event risk incremental to traditional risk factors.…”
Section: The Potential Role Of Non-invasive Imaging For Preventing Acmentioning
confidence: 99%
“…3 This is particularly critical for using imaging for screening purposes among asymptomatic individuals where improved patient outcome must be weighed against risks from imaging and intervention. 93 Thus, a staged approach is likely necessary with the least costly and most benign techniques applied to patients of seemingly low risk for screening purposes and advanced imaging reserved for those deemed at higher risk. For example, ultrasound imaging of carotid artery wall thickness provides prognostic information on acute coronary event risk incremental to traditional risk factors.…”
Section: The Potential Role Of Non-invasive Imaging For Preventing Acmentioning
confidence: 99%
“…16 This strategy is supported by its easier accessibility, perpendicular location relative to the transducer beam, and better reproducibility. 17,18 Although some investigators have suggested averaging multiple segments to include the common carotid, bulb, and internal carotid artery, this is not routinely done, and there remains no clear consensus on which CIMT assessment constitutes the best measurement of atherosclerosis or vascular risk.…”
Section: Technical Issues Related To Cimt Measurementsmentioning
confidence: 99%
“…While a popular subject for debate has been the relative advantages of CAC and CIMT for risk stratification in primary prevention,568 these techniques, as well as CRP measurement, are complementary clinical tools, rather than competitors.…”
Section: Residual Risk Remains a Source Of Concernmentioning
confidence: 99%